2016
DOI: 10.1099/jmm.0.000218
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of two independent real-time PCR assays to detect clinically relevant Mucorales species

Abstract: PCR-based detection of Mucorales species could improve diagnosis of suspected invasive fungal infection, leading to a better patient outcome. This study describes two independent probe-based real-time PCR tests for detection of clinically relevant Mucorales, targeting specific fragments of the 18S and the 28S rRNA genes. Both assays have a short turnaround time, allow fast, specific and very sensitive detection of clinically relevant Mucorales and have the potential to be used as quantitative tests. They were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 34 publications
4
77
0
Order By: Relevance
“…In our cohort, the specificity of Aspergillus and panfungal PCR was similar or better to previous reports with 36%‐94% and 67%‐86% in BAL‐fluid, respectively, while their sensitivities were much lower . There are several potential explanations for the poor sensitivities of our PCR in the BAL‐fluid.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In our cohort, the specificity of Aspergillus and panfungal PCR was similar or better to previous reports with 36%‐94% and 67%‐86% in BAL‐fluid, respectively, while their sensitivities were much lower . There are several potential explanations for the poor sensitivities of our PCR in the BAL‐fluid.…”
Section: Discussionsupporting
confidence: 83%
“…We found that the In our cohort, the specificity of Aspergillus and panfungal PCR was similar or better to previous reports with 36%-94% [19][20][21] and were much lower. 5,7,9,20,21,23,24 There are several potential explanations for the poor sensitivities of our PCR in the BAL-fluid. First, all hematological patients at risk for fungal infection also comprising those without specific infiltrates were included in this study, which could have led to a negative selection of patients without suspected IMD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations